Impact of alcohol marketing on drinkers with Alcohol use disorders seeking treatment: a mixed-method study protocol - Morgane Guillou-Landreat; Antoine Dany; Jean Yves Le Reste; Delphine Le Goff; Amine Benyamina; Marie Grall-Bronnec; Karine Gallopel-Morvan (BMC, 2020)
Abstract Background The marketing of alcohol influences patterns of alcohol consumption. Existing studies have focused, for the most part, on adolescents and the links between exposure to marketing and alcohol initiation. In France, the Evin law, a French exception, was set up in 1991 with the aim of regulating this exposure to marketing, but since 2009 it has been severely compromised. Alcohol consumption causes severe damage, which may be seenfrom 1 standard unit per day and mostly among adults who are regular users of alcohol. In this at-risk population, studies analysing the impact of marketing are sparse. The specific objectives include (i) the evaluation of the perception of alcohol marketing by patients with an AUD (ii) gaining understanding of the links between alcohol marketing and patients with AUD behaviours (iii) the development of alcohol demarketing strategy in patients receiving AUD coaching. Methods Our main objective isto evaluate the impact of marketing on a population with an AUD. The methodology was in 4 steps: step 1 is a pre-test (N = 100) selecting type of alcohol consumed and type of marketing stimuli identified by patients aged 18 + with an AUD. Step 2 is a qualitative study (N = 20), with in-depth interview, to understand links between alcohol marketing and patients with AUD behaviours. Step 3 is a quantitative study(N = 600) to confirm these links and the impact of alcohol marketing on patients with AUD behaviours. Step 4 is an interventional step, including and testing the impact of demarketing intervention on patients with AUD while using the results of the three first steps (N = 120). Discussion This study will contribute to a better definition of the impact of alcohol marketing on patients with AUD and will enable identification of the determinants of this impact. These data will inform the development of interventions that take into account demarketingstrategies on patients under AUD management. Trial registration The Trial registrationregistration number is NCT03876132 , and it was registered on the 15th march 2019.